Pendidikan perilaku untuk anak Sekolah Dasar - Suryati, Suryati; Tamam, Abas Mansur; Supraha, Wido (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Nowadays, there has been a significant shift in the behavior of elementary school-age children, which tends to get worse due to many factors, including the negative influence of social media, lack of guidance from parents, and an educational and societal environment that is not conducive. This research aims to analyze behavioral education for elementary school children. The research method used is library research, which involves using several references, including books, journals, articles, and newspapers related to the research topic. The results of the research state that behavioral education for elementary school children must use appropriate methods to influence and form good behavior in children. Several methods can be used in behavioral education: First, the exemplary method, which is a very effective method for educators (parents and teachers) in educating behavior, in accordance with the development tasks of elementary school-age children, namely the development of morals, values and conscience. Educators use the exemplary foundation of the Prophet Muhammad as the best example. Second, the coaching method which is a method that educators can use to form children's Aqidah, faith and worship and develop morals based on belief in the truth of revelation. Third, the reward and punishment method is the method most often used in behavioral education, because it provides an understanding of responsibility to children, so that in the future they are expected to become disciplined children in all things.